2010
DOI: 10.1097/adm.0b013e3181b95015
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Opinions, and Practice Patterns of Obstetrician-Gynecologists Regarding Their Patients' Use of Alcohol

Abstract: There are few changes in the alcohol-related screening and treatment patterns of ob-gyns since 1999; although perceived barriers and needs have changed. Interventions, including referral resources and continuing medical education training, are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 15 publications
2
52
0
Order By: Relevance
“…One study found, for example, that primary care providers would need to spend 4.4 h per work day to complete all recommended screening and prevention tasks [63]. A more recent survey of obstetric practitioners found little change over time in use of SBIRT to treat alcohol use in pregnancy [64]. More than half reported they did not use a standardized screening tool (57.8%), and older practitioners felt more prepared to screen for hazardous drinking than younger practitioners.…”
Section: Screening and Brief Interventionmentioning
confidence: 96%
“…One study found, for example, that primary care providers would need to spend 4.4 h per work day to complete all recommended screening and prevention tasks [63]. A more recent survey of obstetric practitioners found little change over time in use of SBIRT to treat alcohol use in pregnancy [64]. More than half reported they did not use a standardized screening tool (57.8%), and older practitioners felt more prepared to screen for hazardous drinking than younger practitioners.…”
Section: Screening and Brief Interventionmentioning
confidence: 96%
“…Such findings may be in part explained by growing evidence that SBIRT approaches are challenging to implement due to the time, training, and commitment they require (Yarnall et al, 2003, van Beurden et al, 2012, Kaner et al, 2013, Aalto et al, 2005, DePue et al, 2002). In prenatal care settings, many obstetricians report obstacles such as insufficient time and limited confidence in addressing alcohol use (Anderson et al., 2010). …”
Section: Introductionmentioning
confidence: 99%
“…19 Similar findings have been reported by multiple surveys of physicians providing care for pregnant women, suggesting that few of them fully implement recommended brief intervention strategies. [20][21][22] Advantages of computer delivery Computer-delivered screening and brief intervention may address some of these obstacles and has a number of potential advantages over current approaches. First, some evidence has suggested that only a third of women are assessed for alcohol use during prenatal care visits.…”
Section: Introductionmentioning
confidence: 99%